Science and Human Behavior as a system of psychology: Understanding the book by its structure - Laurenti, Carolina; Lopes, Carlos Eduardo (Perspectivas em Análise do Comportamento, 2023)
Science and Human Behavior (S&HB), published in 1953, was initially written by B. F. Skinner to assist him in his classes for undergraduates at Harvard. At the time of publication, reviews of the book considered the work a “new psychology” and a well-finished portrait of Skinner’s scientific system. This year, S&HB celebrates its 70th anniversary, which may suggest that the book is dated. This paper argues that reading S&HB can still be helpful, even for behavior analysts. To support this thesis, we will discuss the need for a comprehensive reading of that book, respecting its systemic and recursive structure. Through that strategy, we highlight some characteristics of Skinner’s proposal that teaching and research in Behavior Analysis should have paid more attention to.